Neutrophil-to-lymphocyte ratio in females as a predictor of embryo acquisition outcomes after IVF/ICSI treatment: a retrospective study - Shen, Liwen; Chen, Li; Chen, Lifen; Jiang, Huiping; Gu, Huifeng; Lu, Liqun (Frontiers in Endocrinology, 2026)
ObjectiveWe aimed to analyze the correlation between the neutrophil-to-lymphocyte ratio (NLR), and the treatment outcomes for infertile women after in vitro fertilization (IVF) using embryo transfer technology.MethodsThis retrospective study enrolled women with infertility at Huzhou Maternal and Child Health Care Hospital who underwent in vitro IVF procedures. Patient data were collected from a reproductive electronic medical record system. We divided 976 participants into positive and negative groups based on embryo availability after IVF. Age, education level, body mass index, infertility type, etiology, miscarriage history, ovarian stimulation protocols, baseline follicle stimulating hormone levels, anti-Müllerian hormone and NLR were compared in both groups. We investigated the association between NLR and IVF outcomes using logistic regression analysis with multi-model adjustments. The receiver operating characteristic (ROC) curve was used to evaluate the screening efficacy of NLR, The subgroup analysis revealed risk variations among different groups. Finally, we performed sensitivity analysis by modifying control values and conducting logistic regression using NLR quartiles.ResultsMultimodal adjusted logistic regression analysis revealed a significant association between the second quartile of NLR and negative outcomes of IVF treatment, with an OR value and 95% confidence interval of 0.28 (0.10-0.67). The area under the ROC curve was 0.850 <. We observed an interaction between NLR quartiles and infertility types, particularly positive correlations between primary infertility, female-specific infertility factors, and no history of miscarriage with IVF outcomes at the second quartile. When the second quartile was adjusted as a reference value, the three remaining quartiles exhibited statistically significant differences compared to the second quartile (p for trend = 0.045).ConclusionWe recommended dynamically monitoring NLR during the cycle of ovulation induction and advocating individualized inflammatory management based on the cause of infertility to ensure the effectiveness of IVF treatment and prevent resource wastage.